2009
DOI: 10.1063/1.3187831
|View full text |Cite
|
Sign up to set email alerts
|

Droplet formation in a T-shaped microfluidic junction

Abstract: Using a phase-field model to describe fluid/fluid interfacial dynamics and a lattice Boltzmann model to address hydrodynamics, two dimensional (2D) numerical simulations have been performed to understand the mechanisms of droplet formation in microfluidic T-juntion. Although 2D simulations may not capture underlying physics quantitatively, our findings will help to clarify controversial experimental observations and identify new physical mechanisms. We have systematically examined the influence of capillary nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
168
2
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 176 publications
(191 citation statements)
references
References 34 publications
15
168
2
6
Order By: Relevance
“…It clearly shows the plug length depends only on Q. However, Liu and Zhang (2009) suggested that the droplet size also strongly depends on Ca in the squeezing regime, which is consistent with the experimental observations (e.g.…”
Section: Influence Of the Flow Rate Ratiosupporting
confidence: 88%
See 3 more Smart Citations
“…It clearly shows the plug length depends only on Q. However, Liu and Zhang (2009) suggested that the droplet size also strongly depends on Ca in the squeezing regime, which is consistent with the experimental observations (e.g.…”
Section: Influence Of the Flow Rate Ratiosupporting
confidence: 88%
“…When Ca is increased to 0.032 and 0.056, the detachment point will move from the T-junction corner to the downstream as Q increases. In addition, the droplet detachment point gradually moves downstream until a stable jet is formed when Ca and Q increase, which was also observed both numerically (De Menech et al (2008); Liu and Zhang (2009)) and experimentally (Christopher et al (2008)). …”
Section: Influence Of the Flow Rate Ratiosupporting
confidence: 69%
See 2 more Smart Citations
“…The underlying physical properties of lattice Boltzmann schemes are determined via the hydrodynamic moments of the equilibrium distribution functions. The moments of the distribution functions should satisfy [86] (38) where P is the pressure tensor, and is a coefficient which controls the phase interface diffusion and is related to the mobility M of the fluid as follows [86,129],…”
Section: Free-energy Modelmentioning
confidence: 99%